SWOT Analysis for XYZ Shipping Services Competitive Advantage - Adelia, Listy (Dinasti Research, 2022)
This study aims to analyze the competitive advantages of XYZ's delivery service using a SWOT approach. The method used is descriptive qualitative with literature studies as the primary data source. The analysis results show that XYZ's strengths include fast service, an extensive distribution network, and an integrated digital system. Weaknesses include low service responsiveness and a conventional warehouse system. Opportunities stem from the growth of e-commerce, logistics digitalization, and government policy support. Threats include price competition, technological risks, and regulatory changes. Based on these results, SO, ST, WO, and WT strategies are formulated, focusing on optimizing strengths, strengthening innovation, modernizing systems, and mitigating operational risks. These strategies are expected to improve XYZ's competitive position and support business sustainability in the highly competitive delivery service industry.